Analisis Wacana Lisan Pada Interaksi Belajar Mengajar di Kelas VI MIN 2 Kota Bengkulu - Hara Juwita, Hara Juwita (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study was to: (1) describe the structure of conversation in the interaction of teaching and learning of student teachers in class VI MIN 2 Bengkulu City, (2) describe the function of speech language in conversations on teaching and learning interactions of student teachers in class VI MIN 2 Bengkulu City, ( 3) describe the function of the use of particles in conversation in the interaction of teaching and learning of student teachers in class VI MIN 2 Bengkulu City. This study used descriptive qualitative method. The subject of this research is the utterance between teachers and students on teaching and learning interactions in the classroom. The sampling technique in this research is purposive sampling. Data collection techniques used were (1) observation techniques, (2) recording techniques, (3) note taking techniques, and (4) document analysis techniques. The validity of the data in this study used the method triangulation technique. Based on the results of the study it can be concluded: 1) Interactions in learning Indonesian in class VI MIN 2 Bengkulu City are studied based on discourse structure. Existing discourse structure includes lessons, transactions, exchanges, movements, and actions. Learning is the highest unit in discourse analysis. Transactions are used to mark the transition of several topics in learning consisting of one or several exchanges. Exchange is used to mark sub-topics in learning. Motion is used to classify the actions taken by the teacher and students. Follow-up is used to analyze the things that are done by the teacher and students during the learning process. Learning that occurs between teachers and students in class VI MIN 2 Bengkulu can be said to be successful because students can answer most of the questions given by the teacher. 2) The function of language includes three things, namely stating something or providing information that is realized with a declarative sentence, asking for information or asking something that is realized with an interrogative sentence, and giving orders or doing something that is realized with imperative sentences. Even though the language function has its own form, in its application the form and function of the language are not always the same. In other words that the form and function of language are flexible. 3) Particles are forms of language that cannot be interpreted semantically or syntactically. The use of particles in teaching and learning interactions serves as the teacher's response or follow-up on actions taken by students and markers of boundaries in discourse.